KONSELING BEHAVIORISTIK TEKNIK BEHAVIOR CONTRACT UNTUK MENGATASI KECANDUAN MEDIA SOSIAL (TIKTOK) SISWA SMPN 3 BAE - Wulan, Nuning Zumar; Kiswantoro, Arista; Santoso, Santoso (Universitas Muria Kudus, 2023)
The aims of this study are: 1) To describe the factors that cause tiktok social media addiction in class VIII students of SMP N 3 Bae Kudus. 2) To describe the application of behaviorisitc counseling with behavior contract techniques to overcome tiktok social media addiction in class VIII SMP N 3 Bae KudusThis type of research is a qualitative research in the form of a case study conducted at SMP N 3 Bae Kudus. The subjects of this study were 2 class VIII students who had problems with social media addiction (tiktok). Data collection techniques include observation, interviews, home visits, and documentation.The results of the study show that by providing behavioristic counseling services with the Behavior Contract technique, the counselee is able to change problematic behavior into expected behavior, namely the counselee is able to control himself by playing social media excessively, is more focused on studying, the counselee sleeps more regularly, does assignments on schedule, and understand the negative impact of social media addiction.